A CLINICAL STUDY OF TEAR FUNCTIONS IN PATIENTS WITH PINGUECULA BEFORE AND AFTER MEDICAL MANAGEMENT - OJHA, BIMALESH; KATARIA, PANKAJ; CHOUDHARY, PANKAJ; SINGH, POOJA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Purpose: The purpose of the study was to determine the changes in tear functions after medical management of pinguecula. Methods: This interventional prospective study included 70 patients with pinguecula random eyes; 39 males and 31 females, 17–70 years of age (mean±SD: 46.52±16.31 years) for medical management. They were categorized as grade P (0), P (1), and P (2) by slit lamp biomicroscopy. Results: On the basis of statistical analysis applying unpaired t-test, for both the test parameters in P (0) grade of pinguecula patients, the p-values for mean Schirmer-1 test and Tear film break-up time (TFBUT) were 0.93, 0.46, 0.03, and 0.22, 0.002, and <0.0001 for BMM versus AMM at 1 m, 3 m, and 6 m, respectively. These p-values show that there were no significant changes in ST-1 at 1 m and 3 m follow-up after medical management. For TFBUT, p-values show that there were no significant changes at 1 m of follow-up but extremely significant at 3 m and 6 m of follow-up. For P (1) grade of pinguecula patients, the p-values for mean Schirmer-1 test and TFBUT were 0.81, 0.08, 0.0002, and 0.31, <0.0001 and <0.0001 for BMM versus AMM at 1 m, 3 m, and 6 m, respectively. These p-values show that there were no significant changes in ST-1 and TFBUT at 1m follow-up after medical management. While, extremely significant changes at 3 m and 6 m of follow-up in ST-1 as well as TFBUT both. Conclusion: The alteration in schirmer-1 test and TFBUT after medical management with e/d carboxyl methyl cellulose 0.5% and/or e/d fluorometholone 0.1% shows improvement in tear film production and tear film stability after 6 months of follow-up.